Elements of muslim-friendly entertainment in hotel - Zainab 'Aqilah binti Mat Daud (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2018)
It is important for the Muslim-friendly hotels to fully implement Shariah compliance from the entrance to the backdoor. However, Muslim-friendly concepts have not been widely applied by the hotels in Malaysia and therefore, the researcher would like to fill the gaps and conduct a study regarding the facilities of the hotels. The main objectives of this research are to identify entertainments in Islam, to identify entertainments in Muslim-friendly hotels and conventional hotels and to develop criteria for the rating of entertainment elements in hotels. The nature of this research is exploratory and observation studies were performed towards three Muslim-friendly hotels and three conventional hotels with three different star levels, ranging from 3-star hotels to 5-star hotels. Audit checklist was used to garner the data and the confirmation from the experts was collected upon the completion of data collection. The findings of the research resulted in 14 elements that have been the repetition of meaning in the previous research regarding Islamic elements for the entertainment. The highest percentage of 18.87% belonged to Gender Segregation and the lowest percentage belonged to Personal Care as it only encountered two repetitions or citation in literature review (1.89 %). However, the essentiality of each element cannot be observed from the percentage as the levels of maqasid shariah (foundation goals) are deemed more important and reliable. The maslahah (benefit) that needs to be preserved regarding the entertainment at the hotel includes eye care, nutrition or body, property, worship, art and personal safety. The fact that Muslim-friendly Entertainment rules have been widely applied by some of the 3-star to 5-star hotels allows the concept to be seen more believable and applicable by the industry stakeholders. The study was able to provide concrete criteria (fourteen criteria) for the rating of entertainment elements in hotels and the root causes were fully understood by the related stakeholders, both from hotel management side and guests' side. The criteria are gender segregation, channels/music/displays, halal drink, appropriate dress code, halal food, Akhlaq, no night club and information on prayer times, hygiene, cleanliness and Muslim-friendly personal care. Appropriate decoration - not depicting human or animal form, covered & not dark, safety feature - lifeguard and no gambling are required.